Good enough sovereignty, or land as property and territory in Latvia - Dzenovska, D (Taylor & Francis, 2022)
After European Union expansion in the 2000s, Danish farmers went eastward in search of cheap land. In Latvia, they encountered indebted farmers and impoverished rural residents who readily sold their land, while at the same time harbouring resentment towards ‘the Dane’ for undermining Latvia’s sovereignty. In the view of significant segments of the Latvian public, ownership of land and territorial rule were intricately linked. In the view of ‘the Dane’ and the European Union, refusal to separate ownership from rule – or property from sovereignty – was a mark of ‘not-yet-mature’ liberal democratic subjects. While European Union institutions monitored and disciplined the Latvian state’s attempts to juridically restrict foreign land ownership, the Latvian state sought to use financial instruments to limit land sales to foreigners. Drawing on ethnographic analysis of the tensions surrounding the Danish presence in the Latvian countryside and on historical analysis of the shifting regimes of ownership and rule since the beginning of the twentieth century, this article traces the emergence of ‘good enough sovereignty’ as a form of political practice aimed at ensuring continued existence of the Latvian state and Latvian farmers.